Sensory Feedback for Upper-Limb Prostheses: Opportunities and Barriers - Leen Jabban; Sigrid Dupan; Dingguo Zhang; Ben Ainsworth; Kianoush Nazarpour; Benjamin W. Metcalfe (IEEE, 2022)
The addition of sensory feedback to upper-limb prostheses has been shown to improve control, increase embodiment, and reduce phantom limb pain. However, most commercial prostheses do not incorporate sensory feedback due to several factors. This paper focuses on the major challenges of a lack of deep understanding of user needs, the unavailability of tailored, realistic outcome measures and the segregation between research on control and sensory feedback. The use of methods such as the Person-Based Approach and co-creation can improve the design and testing process. Stronger collaboration between researchers can integrate different prostheses research areas to accelerate the translation process.